2018
DOI: 10.1122/1.5030952
|View full text |Cite
|
Sign up to set email alerts
|

Normal stress in magnetorheological polymer gel under large amplitude oscillatory shear

Abstract: In this study, the normal stress in magnetorheological polymer gel (MRPG) under large amplitude oscillatory shear was investigated using experiments and particle-level simulations. Under large amplitude oscillatory shear, an intensely oscillating normal stress was measured with a period of exactly half the strain period. As the amplitude of the strain increased, the peak of the normal stress increased and the trough decreased. Changes in the normal stress were mainly caused by two factors: the Poynting effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Additionally, the rheological behavior is not linear anymore. Two recent examples exploring the largeamplitude oscillatory shear (LAOS) behavior of GMRMs are those of An et al 384 and Pang et al 385 An et al 384 prepared MR materials in self-assembled triblock copolymers. They found that the onset strain towards nonlinear rheology decreases substantially under magnetic fields.…”
Section: Bridging the Gap Between Mrfs And Mresmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the rheological behavior is not linear anymore. Two recent examples exploring the largeamplitude oscillatory shear (LAOS) behavior of GMRMs are those of An et al 384 and Pang et al 385 An et al 384 prepared MR materials in self-assembled triblock copolymers. They found that the onset strain towards nonlinear rheology decreases substantially under magnetic fields.…”
Section: Bridging the Gap Between Mrfs And Mresmentioning
confidence: 99%
“…They found that the onset strain towards nonlinear rheology decreases substantially under magnetic fields. In their turn, Pang et al 385 measured the normal stress in MR materials prepared in polyurethane gels using experiments and particle level simulations. As the amplitude of the strain increased, the peak of the normal stress increased and the trough decreased.…”
Section: Bridging the Gap Between Mrfs And Mresmentioning
confidence: 99%
“…In addition, the area enclosed by the cyclic normal force versus strain curves increases with the increase of applied strain, which can be attributed to the phase difference between the applied shear strain and structural strain. 21 Another interesting phenomenon we can nd from the cyclic normal force-strain curves marked by the green dotted line in Fig. 10(b)-(f) is that, when the shear strain is higher than 40%, normal force exhibits an abrupt change during the transition from loading stage I to unloading stage II (or reverse loading stages III to reverse unloading stage IV), and the abrupt change rate increase along with the increase of shear strain, i.e.…”
Section: Normal Force Of Mr Grease Under Quasi-static Cyclic Shearmentioning
confidence: 99%
“…23,24 To date, the investigations into the normal force of MR materials are only carried out under limited loading conditions, i.e., static (shear rate< 10 À4 s À1 ) and dynamic (shear rate> 10 À1 /s) loadings. 16,17,21 Researches addressing the normal force of MR grease under quasi-static shear (10 À4 s À1 < shear rate < 10 À1 s À1 ) were rarely reported. For real-life engineering applications of MR grease dampers to civil infrastructures, i.e., building and bridge, MR grease is oen subjected to the combination of large deformation and quasi-static shear loadings.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the normal force of MRG is highly dependent on the magnetic field. Gong et al (2012) discussed the nonlinear behavior of normal stress of MR polymer gel under large amplitude oscillatory shear condition (Pang et al, 2018). They found that the alteration of normal stress was mainly influenced by two factors, Poynting effect and excited magnetic field, which are both relevant to the interior microstructures of MR polymer gel.…”
Section: Introductionmentioning
confidence: 99%